Color Tuning of Fluorogens for FAST Fluorogen‐Activating Protein. Issue 12 (2nd February 2021) - Myasnyanko, Ivan N.; Gavrikov, Alexey S.; Zaitseva, Snizhana O.; Smirnov, Alexander Yu.; Zaitseva, Elvira R.; Sokolov, Anatolii I.; Malyshevskaya, Kseniya K.; Baleeva, Nadezhda S.; Mishin, Alexander S.; Baranov, Mikhail S.
Abstract: Using benzylidene imidazolone core, we created a panel of color‐shifted fluorogenic ligands for FAST protein without compromise to the binding efficiency and the utility for live‐cell protein labeling. This study highlights the potential of benzylidene imidazolones derivatives for rapid expansion of a pallet of live‐cell fluorogenic labeling tools. Abstract : A series of color‐shifted fluorogenic ligands for FAST protein without compromise to the binding efficiency and the utility for live‐cell protein labeling are presented. This study highlights the potential of benzylidene imidazolones derivatives for rapid expansion of live‐cell fluorogenic labeling tools.